2013
DOI: 10.4161/rna.23696
|View full text |Cite
|
Sign up to set email alerts
|

New developments in post-transcriptional regulation of operons by small RNAs

Abstract: Small regulatory RNAs (sRNAs) are influential post-transcriptional modulators of gene expression in bacteria. They regulate gene expression by base pairing to target mRNAs, leading to inhibition of translation and/or alteration of mRNA stability. Recently, several sRNAs have been discovered to regulate genes encoded in operons. In some cases, these sRNAs regulate all the genes encoded by the polycistronic mRNA (coordinate regulation) while in other cases, only a select subset of cistrons is controlled by the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 42 publications
0
27
0
1
Order By: Relevance
“…Regulation by sRNAs targeting the 5'UTR and masking the RBS leading to inhibition of translation initiation is well-known in bacteria (Desnoyers et al, 2013). Targeting one or selected internal RBS in a polycistronic mRNA can lead to discoordinated expression of the respective genes, as has been shown, e.g., for Spot42 from Escherichia coli, exclusively affecting GalK level in the galETKM operon by targeting the RBS of galK (Balasubramanian and Vanderpool, 2013). In Archaea, regulatory mechanisms have been identified only for a few sRNAs at the molecular level.…”
Section: Discussionmentioning
confidence: 99%
“…Regulation by sRNAs targeting the 5'UTR and masking the RBS leading to inhibition of translation initiation is well-known in bacteria (Desnoyers et al, 2013). Targeting one or selected internal RBS in a polycistronic mRNA can lead to discoordinated expression of the respective genes, as has been shown, e.g., for Spot42 from Escherichia coli, exclusively affecting GalK level in the galETKM operon by targeting the RBS of galK (Balasubramanian and Vanderpool, 2013). In Archaea, regulatory mechanisms have been identified only for a few sRNAs at the molecular level.…”
Section: Discussionmentioning
confidence: 99%
“…QfsR represses exo polycistronic mRNA and activates flg and traI-trb polycistronic mRNAs (Table 1, Figure 3). Whatever the targets, QfsR directly interacts within the polycistronic molecule and coordinates expression of its encoded genes (Table 1, Figure 2), highlighting the involvement of QfsR in the regulation of polycistronic mRNAs (49). Additional studies are necessary to decipher the mechanism involved.…”
Section: Discussionmentioning
confidence: 99%
“…This seems contradictory to the operon-like genomic organization of the genes. However, it has been shown that the expression of genes in an operon can be discoordinately regulated by means of small noncoding RNAs (sRNAs) (Balasubramanian and Vanderpool 2013). In the case of pyocin S6, such a discoordinate regulatory mechanism might protect the bacterial cell from spending energy in the production of the pyocin molecule, while under ironlimiting conditions, when the target receptors are abundantly expressed, a different regulatory mechanism may stabilize the pyocin transcript.…”
Section: Discussionmentioning
confidence: 99%